2015
DOI: 10.1038/leu.2015.126
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic therapy restores normal hematopoiesis in a zebrafish model of NUP98–HOXA9-induced myeloid disease

Abstract: Acute myeloid leukemia (AML) occurs when multiple genetic aberrations alter white blood cell development, leading to hyperproliferation and arrest of cell differentiation. Pertinent animal models link in vitro studies with the use of new agents in clinical trials. We generated a transgenic zebrafish expressing human NUP98-HOXA9 (NHA9), a fusion oncogene found in high-risk AML. Embryos developed a preleukemic state with anemia and myeloid cell expansion, and adult fish developed a myeloproliferative neoplasm (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 60 publications
2
26
0
Order By: Relevance
“…It remains to be examined, in prospective studies, how either GFI1 36S -homozygous or GFI1 36N -heterozygous or -homozygous patients differ with respect to the response to HDACis and whether the use of HATis might be more beneficial for GFI1 36N -heterozygous or -homozygous patients. Our data are in line with other recent work suggesting that epigenetic therapy could be beneficial for leukemia [54]. However, our data indicate that this has to be performed in a personalized manner.…”
Section: Discussionsupporting
confidence: 92%
“…It remains to be examined, in prospective studies, how either GFI1 36S -homozygous or GFI1 36N -heterozygous or -homozygous patients differ with respect to the response to HDACis and whether the use of HATis might be more beneficial for GFI1 36N -heterozygous or -homozygous patients. Our data are in line with other recent work suggesting that epigenetic therapy could be beneficial for leukemia [54]. However, our data indicate that this has to be performed in a personalized manner.…”
Section: Discussionsupporting
confidence: 92%
“…It has to be noted that LBH589 did not induce differentiation in NHA9-expressing cells as no significant changes in the number of CD11b positive cells were observed by flow cytometry analysis post treatment (data not shown). These observations are in accordance with a recent report suggesting the combination of COX or DNMT inhibitors with HDACi for treatment of NHA9 AML patients, 16 however in this study we identified the molecular rationale for HDACi therapy as well as a panel of target genes downstream of NHA9 that can be used as biomarkers for response to this treatment. Furthermore, our hHP-NH9A cellular model showed sensitivity to markedly lower concentrations of LBH589 (4 n M ) than the recommended doses in preclinical studies and Multiple Myeloma Clinical Trials, 17 , 18 indicating that LBH589 could be safely used as novel targeted therapy for the treatment of NH9A AML patients.…”
supporting
confidence: 92%
“…Ring1A and Ring1B also mediate Meis2 repression in the distal limb bud in a process that is shaped by retinoic acid (RA) signaling (Yakushiji-Kaminatsui et al, 2016. In addition, the DNA methylation status of MEIS gene promoters has been linked to disease, and hypomethylation of the MEIS1 promoter is frequently observed in leukemia (Deveau et al, 2015;Ferreira et al, 2016). Similarly, the histone methyltransferase NSD1 (nuclear receptor SET domain containing protein 1), controls MEIS1 expression through histone tri-methylation of lysines 20 (H4K20me3) and 36 (H3K36me3) at the MEIS1 promoter regions in glioma and neuroblastoma cells, and epigenetic silencing of NSD1 causes MEIS1 upregulation (Berdasco et al, 2009).…”
Section: Fig 3 Meis Controls Chromatin Dynamics (A) Meis Proteins mentioning
confidence: 99%